Effect of humic acid on the growth and yield of two maize (Zea mays L.) cultivars on andisol - Tangguh Prakoso; Endang Sulistyaningsih; Benito Heru Purwanto (Jurnal Ilmu Pertanian, 2020)
One way to improve maize (Zea mays L.) production is through land extension using Andisol land. However, Andisol soil has phosphate (P) fixation problem due to the high amorphous material. Hence, the use of organic material in the form of humic acid that has greater affinity to amorphous minerals is recommended to solve the problem. This research was conducted in February-May 2017 at Tri Dharma field of Faculty of Agriculture, Universitas Gadjah Mada. The Andisol land used has a low available P category from Datar, West Java and Wonosobo, Central Java. This research was arranged in a Randomized Complete Block Design (RCBD), consisting of two factors. The first factor was maize cultivar (Bisi-2 and Pioneer-35). The second factor was the doses of humic acid, consisting of control treatment (without fertilizer and humic acid), NPK without humic acid, and NPK + humic acid at 5%, 10%, and 15%. The percentage of humic acid given, based on the amount of NPK 16:16:16 fertilizer, was 350 kg.ha-1. Fertilization was applied three times 100 kg.ha-1 on 1 WAP, 150 kg.ha-1 at 3 WAP and 100 kg ha-1 at 7 WAP. The results is, humic acid treatment had the same effect with NPK fertilization treatment only and control on P available Andisol soil. Humic acid, also has the same effect with NPK fertilizer treatment in increasing the yield component of 100 seeds weight, dry weight of seeds, harvest index, length of cobs and productivity.